Platypnea-orthodeoxia after fibrotic evolution of SARS-CoV-2 interstitial pneumonia. A case report: Platypnea-Orthodeoxia and pulmonary fibrosis by COVID-19 - Longo, Chiara; Ruffini, Livia; Zanoni, Nicola; Longo, Francesco; Accogli, Rocco; Graziani, Tiziano; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2020)
Platypnea-orthodeoxia syndrome (POS) is a clinical entity characterized by positional dyspnoea (platypnea) and arterial desaturation (orthodeoxia) that occurs when sitting or standing up and usually resolves by lying down. POS may result from some cardiopulmonary disorders or from other miscellaneous aetiologies. We report a case of POS in a patient after fibrotic evolution of SARS-CoV-2 interstitial pneumonia associated with pulmonary embolism. The patient did not have any evidence of an intracardiac/intrapulmonary shunt.